Surgical approaches in patients with oligometastatic non-small cell lung cancer - Bertolaccini, Luca; Pardolesi, Alessandro; Forti Parri, Sergio Nicola; Bonfanti, Barbara; Brandolini, Jury; Solli, Piergiorgio (Journal of Thoracic Disease; Vol 10, No 1 (January 31, 2018): Journal of Thoracic Disease, 2017)
In recent years, retrospective analyses have suggested that an oligometastatic state could exist, but the best evidence to date that a temporary oligometastatic disease exists for lung cancer mainly derives from the survival data on retrospective patients underwent surgical resection of a single M1 site and all intrathoracic disease. The critical determinates of long-term survival include definitive treatment of the primary non-small cell lung cancer (NSCLC), a single organ site of synchronous or metachronous disease, a long disease-free interval between treatment of the primary NSCLC and development of metastases, and the absence of intrathoracic lymph node (N0) disease. The ongoing development of innovative approaches to local therapy and treatment directed to the oligometastatic sites should be defined in future studies.